Exploring the association between herbal medicine usage and drug-induced liver injury: insights from a nationwide population-based cohort study using SCCS in South Korea - Yang, Taehyun; Ahn, Juhee; Won, Sungho; Lee, Sanghun (Frontiers in Pharmacology, 2025)
IntroductionDrug-induced liver injury (DILI) is a significant health concern caused by exposure to pharmaceuticals, over-the-counter medications, herbal remedies, and dietary supplements. The contribution of prescribed herbal medicines to DILI risk remains unclear. This study aimed to evaluate the hepatotoxicity risk associated with traditional Korean medicines (TKMs) using nationwide health insurance claims data.MethodsA tailored cohort of patients diagnosed with DILI (ICD-10 code: K71) between January 2011 and December 2019 was obtained from the Health Insurance Review and Assessment Service. After applying inclusion and exclusion criteria, 672,411 patients were identified. Using a self-controlled case study (SCCS) design, exposures were defined as hospital/clinic visits or medication prescriptions within a 90-day window. Analyses were conducted across three groups: outpatients, inpatients, and patients with liver disease. Relative incidences of DILI were calculated for different exposure scenarios.ResultsOutpatients showed the highest relative incidences of DILI 3–15 days after visiting Western hospitals/clinics or being prescribed commercial drugs, with risk estimates of 1.55 (95% confidence interval [CI]: 1.55–1.56) and 2.44 (95% CI: 2.43–2.44), respectively. These risks gradually declined to baseline levels (1.0). All other groups exhibited similar patterns. In contrast, DILI risks associated with TKM hospital/clinic visits and herbal medicine prescriptions were minimal, with relative risks of 1.01 (95% CI: 1.00–1.01) and 0.99 (95% CI: 0.99–0.99), respectively. However, a mildly elevated risk was observed in patients with liver disease.ConclusionThis nationwide cohort study demonstrates that herbal medicines prescribed by TKM practitioners have minimal impact on DILI risk. Patients with pre-existing liver disease exhibit increased susceptibility to DILI. Differentiating between unregulated herbal products and those prescribed in medical institutions is essential for accurate assessment of hepatotoxicity risk.